EFEKTIVITAS KEBIJAKAN INFORMASI DAN TRANSAKSI ELEKTRONIK DI PEKANBARU - Grace Anjelina Siahaan; Hasim As’ari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
ITE (information and electronic transactions) is a regulation or policy that regulates every network users communication based Internet. Where the function as a state control tool for regulate and protect legally from all crime. Rate of internet using every year is increasing to 42,68 % in riau. The pekabaru government is role as the implementation of UU ITE. But which become the phenomena of UU ITE is society lack appreciation and value the articles of UU ITE is elastic and multitafsir ( importance elements ) The purpose of this study is to find out the effectiveness of policy or UU ITE in Pekanbaru. Whether or not it has been effective in achieving the goals of policy. This research use qualitative methods with descriptive approach and adhesive techniques. Cases and data that are required of both primary and secondary data obtained through observation, interview and documentation and then analysis based on research issues. The results of the study show ITE policy in Pekanbaru has not been effective due to internal and external inhibitors.  Keywords: Implementation, Effectiveness, Information Technology, UU ITE.